Comparison of dexmedetomidine and clonidine as an adjuvant to lignocaine with adrenaline in infiltration anesthesia in tympanoplasty: A randomized controlled trial - Veena Mathur; Pradeep Kumar; Sonam Mittal; Deepika Meena; Maina Singh; Veena Patodi (The Indian Anaesthetists' Forum)
Background: Recent trends in surgical practice involve using local anesthesia for procedures like middle ear tympanoplasty due to its benefits, but patients often experience discomfort. Researchers are investigating alpha-2 agonists like clonidine and dexmedetomidine to enhance pain relief. We conducted a double-blind study comparing dexmedetomidine and clonidine’s effectiveness in extending pain relief after tympanoplasty using local infiltration. Aim and Objective: In light of this context, we undertook a randomized, double-blind investigation to compare the efficacy of dexmedetomidine and clonidine in extending the duration of pain relief via local infiltration for tympanoplasty. Materials and Methods: This prospective, randomized, double-blind study was conducted on total of 60 patients belonging to the American Society of Anesthesiologists Class I and II scheduled for tympanoplasty under local anesthesia. All patients were divided into two groups: Group LC, received local infiltration with 12 mL of lignocaine (2%) with adrenaline (1:200,000) plus clonidine (1 μg/kg) and Group LD, received local infiltration with 12 mL of lignocaine (2%) with adrenaline (1:200,000) plus dexmedetomidine (1 μg/kg). Results: Both the groups were comparable regarding demographic profile, perioperative hemodynamics, and total duration of surgery. Time of onset of analgesia was faster in Group LD (89.53 ± 5.54 vs. 94.17 ± 6.19 s) (P = 0.0034) and total duration of analgesia was also prolonged in Group LD (562.40 ± 24.82 vs. 332.30 ± 12.39 min) (P < 0.0001). Conclusion: We concluded that in comparison to clonidine, dexmedetomidine is more effective in terms of faster onset and prolongation of total duration of analgesia when used with local infiltration anesthesia.